MS2 virus-like particles as a versatile platform for multi-disease vaccines: a review - Zhou, Guodong; Luo, Zhili; Zhang, Zhihui; Cao, Shengliang; Li, Yubao (Frontiers in Immunology, 2025)
The coat protein of the MS2 self-assembles into virus-like particles (VLPs) with a diameter of 26 nm. These VLPs are devoid of the phage genome yet are efficiently recognized by the immune system, eliciting robust humoral and cellular immune responses. The structural characteristics of VLPs position them as a promising platform for the development of vaccines and diagnostic tools. Through genetic engineering, antigenic peptides up to 91 amino acids in length can be densely displayed at the N-terminal β-hairpin (AB loop) of the coat protein. Moreover, the fusion of an exogenous sequence with the 19-nucleotide pac site enables the selective incorporation of heterologous RNA into the VLPs. This feature has facilitated the broad application of VLPs in mRNA vaccine development. In this review, we provide a comprehensive overview of the advancements in MS2 phage coat protein VLP-based vaccine research, with a particular focus on their versatile applications in viral, parasite, chlamydial, and cancer immunotherapy. This work aims to serve as a valuable reference for the continued development of vaccines utilizing MS2 phage coat protein VLPs.